2014
DOI: 10.5152/eurjrheumatol.2014.140045
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid changes and insulin resistance in familial Mediterranean fever

Abstract: Objective: Inflammation is known to alter lipid profiles and to induce insulin resistance. This study was planned to test the hypothesis that familial Mediterranean ferver (FMF) patients and their first-degree asymptomatic relatives may have lipid profile changes and/or insulin resistance, similar to other inflammatory diseases. Material and Methods:We studied 72 FMF patients, 30 asymptomatic first-degree relatives, and 75 healthy controls. Fasting and 2-hour postprandial glucose, insulin, apolipoprotein (Apo)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…In a study by Acay et al [14], lower HDL-C and higher triglyceride concentrations were reported in patients with FMF. Candan et al [15] found the difference only in HDL-C concentrations between FMF and control group. Another study showed that FMF patients had lower concentrations of total cholesterol and HDL-C compared to controls [38].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a study by Acay et al [14], lower HDL-C and higher triglyceride concentrations were reported in patients with FMF. Candan et al [15] found the difference only in HDL-C concentrations between FMF and control group. Another study showed that FMF patients had lower concentrations of total cholesterol and HDL-C compared to controls [38].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, different factors, such as serum lipid changes and endothelial dysfunction, were associated with cardiovascular events [13]. Recent studies showed that FMF patients have an increased risk for cardiovascular events compared with healthy controls, due to increased inflammation and altered serum lipid profile, but discordant results have also been reported on the serum lipid levels in FMF [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…2014 yılında yayınlanan iki çalışmada FMF hastalarında sağlıklı kontrollere göre HDL düzeylerinin anlamlı oranda daha düşük olduğu tespit edilse de diğer küçük örneklem büyüklüğüne sahip çalışmalarda FMF hastalarını ile sağlıklı kontroller arasında lipid profilleri bakımından fark bulunamamıştır. 1,[19][20][21] 2022 yılında yayınlanan 164 FMF hastası ve 160 sağlıklı kontrolün dahil edildiği başka bir çalışmada ise TK, TG ve LDL seviyelerinin FMF grubunda anlamlı oranda daha yüksek olduğu tespit edilmiş fakat HDL düzeyleri iki grupta da benzer bulunmuştur. 22 Çalışmamızda TK ve LDL düzeylerinin beklenenin aksine sağlıklı grupta FMF grubuna göre istatistiksel olarak anlamda oranda daha yüksek olduğu tespit edilirken, TG ve HDL düzeyleri açısından iki grup arasında fark bulunamadı.…”
Section: Introductionunclassified